Hacktivism and Its Status in Hungary - Simon, Béla (Magyar Rendészet, 2016)
In recent years the definition of Hacktivism has entered mainstream communication. Our everyday lives are defined by info-communication devices, almost like a house of cards in the wind. This statement is verified by several scientific sources. Nevertheless, according to other pieces of news, this house of cards might as well be destroyed by a secret movement — called hacktivists — at any time. In this study I try to examine whether the news on hacktivist movements in Hungary have sufficient grounds, or it is just the demonization of the phenomenon.